Effects of sensitive electrical stimulation based cueing in Parkinson's disease: a preliminary study - Benoît Sijobert; Christine Azevedo-Coste; David Andreu; Claudia Verna; Christian Geny (PAGEPress Publications, 2016)
This study aims to investigate the effect of a sensitive cueing on Freezing of Gait (FOG) and gait disorders in subjects suffering from Parkinson's disease (PD). 13 participants with Parkinson's disease were equipped with an electrical stimulator and a foot mounted inertial measurement unit (IMU). An IMU based algorithm triggered in real time an electrical stimulus applied on the arch of foot at heel off detection. Starting from standing, subjects were asked to walk at their preferred speed on a path comprising 5m straight, u-turn and walk around tasks. Cueing globally decreased the time to achieve the different tasks in all the subjects. In "freezer" subjects, the time to complete the entire path was reduced by 19%. FOG events occurrence was lowered by 12% compared to baseline before and after cueing. This preliminary work showed a positive global effect of an electrical stimulation based cueing on gait and FOG in PD.